CURRENT STATE OF MINERAL BASE OF TITANIUM DEPOSITS OF UKRAINE - Ganzha, O.; Kuzmanenko, H.; Okholina Т.; Remezova О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The current state of titanium deposits in the world and Ukraine’s place in the world of titanium ore reserves are analyzed. The list of leading countries in terms of reserves of loose titanium-zirconium ores and the dynamics of production is given. There is no regularity of the ratio of countries in terms of reserves and countries in terms of production. A map of the countries to which Ukraine exports titanium raw materials and the dynamics of titanium dioxide prices over the past 5 years are presented. The list of available mining enterprises for enrichment and production of titanium products within Ukraine is given. The general characteristic of the mineral resource base of titanium of Ukraine with the map of the current state of ilmenite and complex zircon-ilmenite placers of the Ukrainian Placer Province is provided.